The benefits of dexmedetomidine for pain mitigation after cautery disbudding in calves - Liu, Tsung-Ching; Chiang, Chen-Fei; Ho, Thomas Chia-Tang; Chan, Jacky Peng-Wen (The Thai Journal of Veterinary Medicine, 2023)
The purpose of this study was to determine the effect of dexmedetomidine (DEX) alone on pain mitigation following cautery disbudding in calves. A total of 21 calves were randomly divided into three groups: sham-disbudded control with placebo (S, n = 8); hot-iron disbudded after placebo (D, n = 6); hot-iron disbudded after 0.01 mg/kg of DEX (DeD, n = 7). The pain-related responses measured included serum cortisol levels, struggling scores, pain-related behaviors and other physiological values. The results indicated that the struggling scores, the cortisol concentrations from +10 to +60 min after disbudding and the area under curve of cortisol profiles in the D group were significantly higher than those in the S and DeD groups. The frequencies of ear flicking were significantly or numerically lower in calves treated with DEX when compared to calves in the D group. In conclusion, the administration of DEX alone could effectively eliminate serum cortisol rise and mitigate the pain reactions during and after disbudding, indicating that DEX may sufficiently reduce possible discomfort, leading to improved welfare during the disbudding procedure in calves.